Sejarah Eksodus Masyarakat Arab Hadrami Yaman ke Makassar - Muhammad Sauqi Nur; Febri Priyoyudanto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to provide deeper insight into the historical dynamics and impact on the region. In analyzing the data, the authors used qualitative methods to understand more deeply the events and motivations behind the exodus of the Yemeni Hadrami Arab Community to Makassar. Primary data from historical documents and trade letters are analyzed narratively and interpreted to identify important patterns and events. Apart from that, secondary data is used to provide a broader picture of the role of the Arab Hadrami Community in Makassar at that time. The exodus of the Arab Hadrami Community to Makassar is an important event in Indonesian history. In the 17th century, they migrated from Hadramaut, Yemen, to Indonesia, especially South Sulawesi. Their goals included trade, the spread of Islam, education, and the formation of mixed families. Hadrami Arab traders brought various trade goods, such as silk cloth and spices, to trade with the local population. This trade had a significant impact on the local economy and helped make Makassar an important trading center.